Battling Western imperialism : Mao, Stalin, and the United States - Sheng, Michael M., 1950- (Princeton University Press, 1997)
One of the central issues in the study of the Chinese Communist Party and its foreign policy is its relations with Moscow. Was the CCP a Chinese nationalist party antagonistic to an intrusive Soviet Union or was it rather an internationalist party with ideological-political and strategic-military ties to Moscow, faithfully adhering to Marxist-Leninist principles as well as to Stalin's policy advice? For the past two decades a number of historians have argued that the CCP was a nationalist movement and that the United States missed its opportunity to establish friendly relations because U.S. leaders were blinded by fears of an international Communist threat. In his provocative book, Michael Sheng strongly challenges this position. On the basis of extensive new information obtained from recently available Chinese sources, Sheng demonstrates that the foreign policy of the CCP under Mao Zedong did, in fact, follow the directions recommended by Joseph Stalin.